A new Suzuki synthesis of triphenylethylenes that inhibit aromatase and bind to estrogen receptors α and β. Issue 21 (1st November 2016) - Zhao, Li-Ming; Jin, Hai-Shan; Liu, Jinzhong; Skaar, Todd C.; Ipe, Joseph; Lv, Wei; Flockhart, David A.; Cushman, Mark
Graphical abstract: Abstract: The design and synthesis of dual aromatase inhibitors/selective estrogen receptor modulators (AI/SERMs) is an attractive strategy for the discovery of new breast cancer therapeutic agents. Previous efforts led to the preparation of norendoxifen (4 ) derivatives with dual aromatase inhibitory activity and estrogen receptor binding activity. In the present study, some of the structural features of the potent AI letrozole were incorporated into the lead compound (norendoxifen) to afford a series of new dual AI/SERM agents based on a symmetrical diphenylmethylene substructure that eliminates the problem of E, Z isomerization encountered with norendoxifen-based AI/SERMs. Compound12d had good aromatase inhibitory activity (IC50  = 62.2 nM) while also exhibiting good binding activity to both ER-α (EC50  = 72.1 nM) and ER-β (EC50  = 70.8 nM). In addition, a new synthesis was devised for the preparation of norendoxifen and its analogues through a bis-Suzuki coupling strategy.